Preschool Minority Children’s Persian Vocabulary Development: A Language Sample Analysis - Farangi, Mohamad Reza; Mehrpour, Saeed (Frontiers in Psychology, 2022)
This study investigated the effects of background television and family socioeconomic status on minority children’s Persian vocabulary development. To this end, 80 Iranian pre-school children (aged 5 to 6 years old) from two minority groups of Arabs and Turks were selected using stratified random sampling. These children were able to use two languages simultaneously, i.e. one was their mother tongue which was either Arabic or Azari and the other was their first language which was Persian. Based on their exposure to background TV (high background vs low background) and their level of socio-economic status (high SES vs low SES), four groups were formed. Children’s vocabulary development was measured through a 15-minture interview by the language experts (PhD in applied linguistics) before and after the ten-week study. The vocabulary measures included total number of utterances produced, total number of words produced, total number of new words produced and mean length of argument. A series of repeated measures and mixed ANOVA tests were used to examine the data. The results showed significant improvement of children’ Persian vocabulary scores in the posttest for all groups as well as higher and significant means for the children in the high socio-economic-high background TV group. Moreover, the results showed that the background TV can be advantageous for families with a low socio-economic status as it may compensate for some linguistics gaps in these families including lower amount of child-parent interaction, play, parents’ level of literacy, etc. These results have some implications for minority language studies, first and second language studies and sociological studies.